Sketches on Truth and "Method" in "The Origin of the Work of Art" by Martin Heidegger Jonathan Eduardo Alvarado Ramos - Alvarado Ramos, Jonathan Eduardo (2019)
In this paper, sketches are given on the notion of truth as de-concealment and the "method" of Heidegger in the lecture of "The origin of the work of art". The question that allows us to open our text is: What does Heidegger intend when he asks about the origin of the work of art? From this question we will describe the Heideggerian notions of origin (Ursprung), truth (Unverborgenheit), world (Welt), earth (Erde). Finally, we will examine how these notions differ from traditional concepts and point to an area prior to metaphysics or aesthetics